Altered functional connectivity to stressful stimuli in prenatally cocaine-exposed adolescents. (1st November 2017) - Zakiniaeiz, Yasmin; Yip, Sarah W.; Balodis, Iris M.; Lacadie, Cheryl M.; Scheinost, Dustin; Constable, R. Todd; Mayes, Linda C.; Sinha, Rajita; Potenza, Marc N.
Highlights: Prenatal cocaine exposure (PCE) may impact youth. PCE versus non-exposed youth showed less parietal connectivity to stress stimuli. PCE versus non-exposed youth showed more parietal connectivity to neutral stimuli. Parietal connectivity showed stress vs. neutral differences in non-exposed youth. Craving scores correlated with corticolimbic connectivity in PCE youth. Abstract: Background: Prenatal cocaine exposure (PCE) is linked to addiction and obesity vulnerability. Neural responses to stressful and appetitive cues in adolescents with PCE versus those without have been differentially linked to substance-use initiation. However, no prior studies have assessed cue-reactivity responses among PCE adolescents using a connectivity-based approach. Methods: Twenty-two PCE and 22 non-prenatally drug-exposed (NDE) age-, sex-, IQ- and BMI-matched adolescents participated in individualized guided imagery with appetitive (favorite-food), stressful and neutral-relaxing cue scripts during functional magnetic resonance imaging. Subjective favorite-food craving scores were collected before and after script exposure. A data-driven voxel-wise intrinsic connectivity distribution analysis was used to identify between-group differences and examine relationships with craving scores. Results: A group-by-cue interaction effect identified a parietal lobe cluster where PCE versus NDE adolescents showed less connectivity during stressful and more connectivity during neutral-relaxing conditions. Follow-up seed-based connectivity analyses revealed that, among PCE adolescents, the parietal seed was positively connected to inferior parietal and sensory areas and negatively connected to corticolimbic during both stress and neutral-relaxing conditions. For NDE, greater parietal connectivity to parietal, cingulate and sensory areas and lesser parietal connectivity to medial prefrontal areas were found during stress compared to neutral-relaxing cueing. Craving scores inversely correlated with corticolimbic connectivity in PCE, but not NDE adolescents, during the favorite-food condition. Conclusions: Findings from this first data-driven intrinsic connectivity analysis of PCE influences on adolescent brain function indicate differences relating to PCE status and craving. These findings provide insight into the developmental impact of in utero drug exposure.